2018
DOI: 10.1055/s-0038-1641571
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Treatment of Peripheral Nerve Pathology

Abstract: High-resolution ultrasound serves as a fast, accessible, reliable, and radiation-free tool for anatomical and dynamic evaluation of various peripheral nerves. It can be used not only to identify and diagnose peripheral nerve and perineural pathology accurately but also to guide various nerve and perineural interventions. We describe the normal and pathologic appearances of peripheral nerves, the pathologies commonly affecting the individual peripheral nerves, and the current ultrasound-guided peripheral nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 58 publications
(80 reference statements)
0
31
0
Order By: Relevance
“…Ultrasound is the first choice level technique to image the nerve according to the last Guidelines of the European Society of Musculoskeletal Radiology (ESSR) [ 26 ] and widely applicated in ultrasound-guided injections around the nerve [ 27 , 28 ], we attempted to use ultrasound to identify the 3D distribution, which would help to avoid damaging LFCN from cutting to the suture. This is different from traditional skin marking protocol using ultrasound guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is the first choice level technique to image the nerve according to the last Guidelines of the European Society of Musculoskeletal Radiology (ESSR) [ 26 ] and widely applicated in ultrasound-guided injections around the nerve [ 27 , 28 ], we attempted to use ultrasound to identify the 3D distribution, which would help to avoid damaging LFCN from cutting to the suture. This is different from traditional skin marking protocol using ultrasound guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with no 3D location, the identi cation of LFCN was a great option to signi cantly decrease the rate of DAA-induced LFCN injury. Similar studies, which focused on the treatment of meralgia paresthetica of LFCN or nerve block conduction using ultrasound guiding technique, also demonstrated that ultrasonographic images provided precious and visible position that would be helpful to a safe and effective treatment, especially for nerves with anatomical variation and some branches [29][30][31].…”
Section: Discussionmentioning
confidence: 81%
“…With the typical in-plane approach, 15 16 the puncture site is placed somewhat away from the transducer footprint to allow for a shallower approach relative to the probe. A shallower approach increases the angle between the US beam and needle ( Fig.…”
Section: Needle Selection and Positioningmentioning
confidence: 99%
“…2a, b ). The visibility of the needle is significantly increased with angles > 40 degrees 1 16 17 and is maximal if perpendicularly oriented, with the needle acting as a specular reflector. 2 A variety of techniques have been introduced in US machines and needle technologies to improve visualization, especially when optimal approach angles cannot be achieved.…”
Section: Needle Selection and Positioningmentioning
confidence: 99%
See 1 more Smart Citation